ANALYSIS OF ARTICLE 177 LETTER (D) LAW NUMBER 7 OF 2017 CONCERNING GENERAL ELECTIONS REGARDING WOMEN'S REPRESENTATION QUOTAS IN LEGISLATIVE ELECTIONS 2019 IN TANGERANG CITY - Nilasari, Nur Apisha; Nazah, Farida Nurun; Ahmad, Dwi Nur Fauziah (Universitas Muhammadiyah Tangerang, 2024)
Women's participation in politics is essential for the policy formation process. The aim of women's participation in parliament is to create accommodative and substantial political policy making. The right of politicized women was legislated through Law Number 68 of 1945. The aim of the research is to determine the representation of female legislative candidates who have met the qualifications of the Tangerang City Electoral Commission in the 2019 Election and to assess the contribution of women in parliament at the Tangerang City Regional Legislative Council to political policy making. This research is empirical, utilizing data collection methods such as observation, interviews, and documentation at the Electoral Commission and Regional Legislative Council offices in Tangerang City. The research results show a significant disparity in the representation of female legislative candidates in Tangerang City who have met the qualifications set by the Tangerang City Electoral Commission qualifications has a very unequal number. In the 2019 election, 648 candidates qualified for the permanent candidate list, comprising 411 men and 234 women from a total of 16 political parties. Meanwhile, 50 people were appointed as members of the Tangerang City Regional Legislative Council, comprising 44 men and 6 women, with a percentage of 12%. The contribution of women as members of the Tangerang City Regional Legislative Council in making political policies has been sufficiently considered. This is proven by the implementation of socialization programs at the women's protection service and the establishment of policies related to public health services (Kesta).Keywords : Women's Representation, Legislative Elections, Political Policy